PROPERTIES OF MODIFIED CONCRETE FOR SPECIAL PURPOSE STRUCTURES - Rudenko, D. V. (Science and Transport Progress, 2018)
Purpose. The paper is aimed at developing the scientific fundamentals of new-generation monolithic concrete technology for special purpose structures by controlling the processes of structure formation of a modified cement system under natural hardening conditions. Methodology. The kinetics of interaction between the cement system and aggregates was evaluated by microcalorimetry. The measurements were carried out continuously for 24 hours after preparation of the mixture. The differential and integral characteristics of the heat release of the solidifying system were recorded. Investigation of the rheological properties of concrete mixtures was carried out on the mixtures with 10...15 cm consistency. The microhardness of contact layers was investigated on concrete cubes with dimensions from 20×20×20 to 50×50×50 mm. When determining the structural characteristics, x-ray phase and differential-thermal analyzes of the concrete cement matrix were used. Infrared spectroscopy was used to determine the effect of physicochemical modification on the cement system. Tensile creep was studied over a wide load range from 0.2Rt to 0.8Rt. Findings. It is determined that the reason for changing the concrete properties of natural hardening is the change in its hygrometric and thermal state, as well as the harmonic fluctuations of these environmental factors. The hygrometry of concrete depends on the thermal moisture conditions of the environment, the type and composition of concrete, the massiveness of concrete elements. An analysis of these factors and experimental data made it possible to establish the exponential dependence of the change in the hygrometric state of monolithic natural hardening concrete. The change in the moisture state of concrete makes it possible to predict its volumetric deformations. Originality. For the first time, the features of the structure formation of a modified cement system are established, consisting in the fact that magnesium chloride hydrate crystals grow rapidly in the space between hydrated clinker minerals, and the resulting mechanical cohesion defines the development of initial strength and rigidity. Since the free growth of crystals is hampered by a lack of space, the crystals mutually intergrow, forming a dense structure, contributing to the growth of strength. The developed organo-mineral modifying complex provides disperse reinforcement of the cement matrix of concrete. Practical value. The obtained dependences of structural concrete stresses make it possible to analyze their effect on the structure of modified concrete: to determine the probability of formation around the filler particles of the plastic flow zone, the material microcrack formation zone, the crack initiation period, the microcrack onset conditions, and the change of elasticity modulus of the material caused by microcracks in its structure. Disperous modification of cement matrix allows to obtain durable concrete of special purpose with design operational properties. The developed binder disperse modification technology, the established features of the structure formation mechanism for the modified cement system, as well as the use of the principle of congruence of a complex of technological influences to the physico-chemical processes of hydration of clinker minerals allowed developing the scientific fundamentals for the special purpose concrete technology. This helps to expand the use of modified concrete in various types of construction.